Pendekatan Pemerosesan Informasi - Fauziah Nasution; Zahwa Nazhifah Limbeng; Khairunnisa; M. Habib Rifki Nasution (CV Putra Publisher, 2023)
Information processing is the process students use to collect information, monitor it, and develop information-related strategies using an approach that emphasizes memory and thinking patterns. The purpose of writing this article is to understand more thoroughly about information processing. The method used in this article is literature study. The result is, it can be understood that information processing is a way for people to process information, observe, and develop strategies based on that information. There are a number of teaching models of information processing theory. For students, information processing utilized in the field of stimulus control, acts as a collection of components of directive data, allowing students to realize solutions to concept development problems so that they can control stimuli.